Influence of Strain‐hardening on the Bending Strength and Rotation Capacity of Welded I‐section Beams. Issue 4 (14th September 2022) - Studer, Patrick; Taras, Andreas
Abstract: The bending strength and rotation capacity of welded I‐section beams made of four different steel grades with varying strain‐hardening characteristics are investigated in this paper. Therefore, four point bending tests are carried out on beams with different cross‐sections. These cross‐sections are assigned to cross‐section class 1 and 3 respectively and thus denote cross‐sections with different design approach. The central areas of the beams were scanned to determine the initial imperfections. The newly developed steel grade, which exhibits a pronounced hardening behavior, achieves a higher bending strength as well as a greater rotational capacity compared to the conventional steel grades. With DIC measurements, the deformation field as well as the resulting strains and stresses over the height of the web could be investigated during the tests. By parameterized numerical simulations, it was possible to identify the shape of the initial imperfection as relevant parameter. By comparing the outcome of the numerical simulations with the experimental investigations, a verified numerical model could be developed, which can be used for further investigations on cross‐section classification.